(untitled) (Research, Society and Development, 2020)
The present study aimed to conduct an integrative review on Autistic Spectrum Disorder and eating habits, specifically analyzing the eating habits of autistic people and the factors that influence the eating habits of children and adolescents with ASD. It is an integrative literature review, of a qualitative and exploratory nature, with a theoretical approach. Searches for article references were made through an electronic database (Scielo, Google Acadêmico, BVS, LILACS, PUBMED). For the survey survey, the descriptors were used: "autism spectrum disorder", "behavior", "food", "nutrition", "children", "adolescents", in Portuguese and English, registered in the Descriptors in Science of the Health (DeCS). The search resulted initially in 18 articles, which addressed the descriptors selected for research. After the analysis and the thorough reading respecting the inclusion and exclusion criteria, 10 articles remained for analysis, in the period from 2018 to 2020. In the studies analyzed it was possible to observe a high consumption of processed foods and a low food variety, in addition to a high refusal to include new foods in the diet, which may cause micronutrient deficiency and problems in the development of these children and adolescents with ASD. It is concluded that the eating habits of children and adolescents showed changes in 100% of the studies analyzed, demonstrating a preference for processed foods and showing a high rate of overweight and obesity, as well as a deficiency of vitamins and minerals. Evidencing the risk of long-term nutritional problems, since childhood habits have a direct influence on adult life.